Estudio de factibilidad para un sistema de control de reservaciones de boletos en el terminal terrestre de Babahoyo. - Sánchez Bermúdez, Lady (2018)
The present case study consists in carrying out a Feasibility study for a ticket reservation control system in the Babahoyo terminal. The research subline of this project is the development of computer systems. Currently the increase of users in cities, influences the supply of transport for the development of daily activities of people who need to move, over time the need arose that various means of ground transportation for mobilization are implemented of the populations. The land transport that is used in the Babahoyo city serves to move from one place to another, it is public transport, which leads users to get used to the schedules and routes they offer. This also varies their costs due to different factors such as the distance between the destinations and the quality of the service. The demands of travel and use of the services of the terrestrial terminal of the city of Babahoyo have generated a growth in their users therefore a notable lack of control in the reservation process for the services of the same. The purpose of this case study is to develop a feasibility analysis to solve the inconveniences that arise in the transportation of passengers from the Babahoyo terrestrial terminal and for this reason you can have a vision of what they are and what should be improved.